A Direct Measurement of Atmospheric Dispersion in N-band Spectra: Implications for Mid-IR Systems on ELTs - Skemer, A; Hinz, P; Hoffmann, W; Close, L; Kendrew, S; Mathar, R; Stuik, R; Greene, T; Woodward, C; Kelley, M (2009)
Adaptive optics will almost completely remove the effects of atmospheric turbulence at 10 microns on the Extremely Large Telescope (ELT) generation of telescopes. In this paper, we observationally confirm that the next most important limitation to image quality is atmospheric dispersion, rather than telescope diffraction. By using the 6.5 meter MMT with its unique mid-IR adaptive optics system, we measure atmospheric dispersion in the N-band with the newly commissioned spectroscopic mode on MIRAC4-BLINC. Our results indicate that atmospheric dispersion is generally linear in the N-band, although there is some residual curvature. We compare our measurements to theory, and make predictions for ELT Strehls and image FHWM with and without an atmospheric dispersion corrector (ADC). We find that for many mid-IR applications, an ADC will be necessary on ELTs.